Severe Combined Immunodeficiency: A Case Series and Review from a Tertiary Pediatric Hospital - Shahrzad Fallah; Mehrnaz Mesdaghi; Mahboubeh Mansouri; Delara Babaei; Abdollah Karimi; Seyed Alireza Fahimzad; Shahnaz Armin; Sedigheh Rafiei Tabatabaei; Roxana Azma; Ghamartaj Khanbabaee; Bahram Bashardoost; Mehrdad Amirmoeini; et al. (Iranian Journal of Allergy, Asthma and Immunology, 2018)
Severe combined immunodeficiency syndrome (SCID) is a life-threatening condition leading to early infant death as a result of severe infection, due to impaired cellular and humoral immune systems. Various forms of SCID are classified based on the presence or absence of T cells, B cells and natural killer cells. Patients usually present with recurrent infections and failure to thrive. Definitive treatment is hematopoietic stem cell transplantation. To achieve the best outcome, it should be performed prior to the development of severe infection. In This study, we described 10 patients (6 male and 4 female) with SCID who were admitted to Mofid Children Hospital, Tehran, Iran, from 2006 to 2013. We reviewed patients’ clinical manifestation, laboratory data, family history and outcome. The mean age at the time of diagnosis was 131.8 days. One patient had non-consanguineous parents. Seven patients received BCG vaccine before the diagnosis of SCID, three of them showed disseminated BCG infection. One patient presented with invasive pulmonary aspergillosis. Flow cytometric analysis showed T⁻B⁺NK⁻ in three patients, T⁻B⁻NK⁺ in five patients, T⁻B⁻NK⁻ in one patient, and T⁻B⁺NK⁺ in one patient. This study highlights the importance of early diagnosis and patient referral before the occurrence of serious infection.